Study guides

☆☆

Q: What is the answer to the equation 6 x - a -3 x plus a?

Write your answer...

Submit

Still have questions?

Related questions

The answer to the equation 3 2x-4 plus 2 x plus 7 6 is 34x + 72.

Using the quadratic equation formula: x = -3 - the square root of 3 or x = -3 + the square root of 3

If 3x + 3 = 2x + 6 then 3x - 2x = 6 - 3 x = 3

2x + 3 = 6 2x = 3 x = 3/2 = 1.5

The value of X in the equation 2.9 plus x plus 7.5 = 6 is -4.4.

In the equation x + 9 = 6, x is negative.

2x - 6 = 3x + 3: * Firstly, subtract 2x from both sides of the equation: -6 = x + 3 * swap the equation, so that "x" is on the left-hand side (to make things easier): x + 3 = -6 * subtract 3 from both sides of the equation, to give: x = -9

3 is the true!

x = 5 or x = 6

Strictly speaking, it is a quadratic equation in x. x2 + x = 6 => x2 + x - 6 = 0 => (x+3)*(x-2) = 0 => x = -3 or x = 2

x plus 37467 is referred to as a linear equation since it can be plotted in the x-y graph.

The value of X in the equation 2x-1-6 5 plus 6x is -3.

People also asked